Hegemony and Fantasy in Irish Drama, 1899-1949 - Murphy, P. author. aut Link
IX, 266 p.
Keywords: Hegemony and Fantasy in Irish Drama, 1899-1949 offers a theoretically innovative reconsideration of drama produced in the Irish Renaissance, as well as an engagement with non-canonical drama in the under-researched period 1926-1949.